Renin Angiotensin Aldosterone System Antagonism in 2019 Novel Coronavirus Acute Lung Injury. (4th April 2021) - Ventura, Davide; Carr, Amy L; Davis, R Duane; Silvestry, Scott; Bogar, Linda; Raval, Nirav; Gries, Cynthia; Hayes, Jillian E; Oliveira, Eduardo; Sniffen, Jason; Allison, Steven L; Herrera, Victor; et al.
Abstract: It has been established that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) uses angiotensin-converting enzyme 2 (ACE2), a membrane-bound regulatory peptide, for host cell entry. Renin-angiotensin-aldosterone system (RAAS) inhibitors have been reported to increase ACE2 in type 2 pneumocyte pulmonary tissue. Controversy exists for the continuation of ACE inhibitors, angiotensin II receptor blockers, and mineralocorticoid receptor antagonists in the current pandemic. ACE2 serves as a regulatory enzyme in maintaining homeostasis between proinflammatory angiotensin II and anti-inflammatory angiotensin 1, 7 peptides. Derangements in these peptides are associated with cardiovascular disease and are implicated in the progression of acute respiratory distress syndrome. Augmentation of the ACE2/Ang 1, 7 axis represents a critical target in the supportive management of coronavirus disease 2019–associated lung disease. Observational data describing the use of RAAS inhibitors in the setting of SARS-CoV-2 have not borne signals of harm to date. However, equipoise persists, requiring an analysis of novel agents including recombinant human-ACE2 and existing RAAS inhibitors while balancing ongoing controversies associated with increased coronavirus infectivity and virulence.